Síntese e avaliação da atividade antifúgica de análogos de butenafina - Ana María Garzón Porras (2015)
Schiff bases, secondary amines and their N-methylamines analogous to antifungal butenafine were synthesized. The synthesis was efficient, simple and rapid for the first two groups of compounds mentioned, which were obtained with global yields higher than 94% at most. In contrast, overall yields for the synthesis of N-tertiary methylamines weregenerally above 66% for the benzylic amine, which are better substrates than the phenylic amines. Schiff bases, secondary and tertiary amines and their hydrochlorides were then evaluated for antifungal potential clinical interest. The fungus Cryptococcus gattii ATCC 32608, ATCC 16913 Aspergillus fumigatus, Trichophyton interdigitale and Microsporumgypseum were then studied in order to determine the minimum inhibitory concentration (MIC) of test-compounds required to inhibit 100% of microbial growth. The N-methylamines were more active than the corresponding secondary amines. The hydrochlorides, by way of example5b.HCl, 8b.HCl, 2c.HCl, 5c.HCl and 8c.HCl, and the free amines 5b, 5c and 8c were in most cases as active as antifungal reference (butenafine; MIC < 4 ug.L-1) for three of the four fungi tested. Notably, the presence of the naphthyl and 4-tert-butylbenzyl group, as well as lower basic character of the nitrogen atom in aqueous medium, contributed to increasing theantifungal activity of the tested compounds. The results indicate that the hydrochloride 5b.HCl, 8b.HCl, 2c.HCl, 5c.HCl and 8c.HCl, further it is synthesized in overall yields greater than 67%, have shown promising antifungal against the fungus C. gattii ATCC 32608, T. interdigitale and M. gypseum, may be used as a platform for the development of even morepotent antifungals.